Focus on Chemistry of the 10-Dioxane-nido-7,8-dicarba-undecahydrido Undecaborate Zwitterion; Exceptionally Easy Abstraction of Hydrogen Bridge and Double-Action Pathways Observed in Ring Cleavage Reactions with OH- as Nucleophile - Bakardjiev, Mário; El Anwar, Suzan; Bavol, Dmytro; Růžičková, Zdeňka; Grűner, Bohumír (Molecules, 2020)
Ring cleavage of cyclic ether substituents attached to a boron cage via an oxonium oxygen atom are amongst the most versatile methods for conjoining boron closo-cages with organic functional groups. Here we focus on much less tackled chemistry of the 11-vertex zwitterionic compound [10-(O-(CH2-CH2)2O)-nido-7,8-C2B9H11] (1), which is the only known representative of cyclic ether substitution at nido-cages, and explore the scope for the use of this zwitterion 1 in reactions with various types of nucleophiles including bifunctional ones. Most of the nitrogen, oxygen, halogen, and sulphur nucleophiles studied react via nucleophilic substitution at the C1 atom of the dioxane ring, followed by its cleavage that produces six atom chain between the cage and the respective organic moiety. We also report the differences in reactivity of this nido-cage system with the simplest oxygen nucleophile, i.e., OH-. With compound 1, reaction proceeds in two possible directions, either via typical ring cleavage, or by replacement of the whole dioxane ring with -OH at higher temperatures. Furthermore, an easy deprotonation of the hydrogen bridge in 1 was observed that proceeds even in diluted aqueous KOH. We believe this knowledge can be further applied in the design of functional molecules, materials, and drugs.
Keywords: dusík; Dioxanes; dioxany; Temperature; bor; teplota; halogeny; Boranes; Halogens; borany; Nitrogen; Boron